(untitled) (Global Journal of Management and Business Research, 2012)
The dichotomy in policy making regarding the hotel industry and air transport, makes it imperative for the government to formulate clear policy processes in order to avoid conflicting situations among stakeholders. This paper looks at the various issues regarding policy theories and examines the various theories that have made their mark in other countries. It has often been contended that the national carrier, the hotel industry and government have often been looking in different directions instead of coming up with consistent policies common to all stakeholders where all could deploy efforts to consolidate the tourism industry and at the same time contribute to economic growth. Several policy theories are available namely Policy Network Analysis (PNA), Advocacy Coalition Framework (ACF), Prospects Theory, Power Elites Theory and Community organization Theory among others. Most of the above are analyzed and compared and the two theories that come close are the PNA and ACF with a preference for the latter for various reasons developed in the paper. Governments have to pay considerable attention to new policies in the implementation of an open sky policy and must assess its impacts so as to #x2018;protect#x2019; their respective national carriers.